Quick Systemic Lupus Activity Questionnaire (Q-SLAQ): a simplified version of SLAQ for patient-reported disease activity - Susanne Pettersson; Iva Gunnarsson; Andreas Jönsen; Christopher Sjöwall; Dag Leonard; Vera Illescas-Bäckelin; Estelle Trysberg (Lupus Science and Medicine)
Objectives Most indices of disease activity in SLE combine physicians’ assessments and laboratory tests. However, there is also a need to capture patients’ perspectives of disease activity. Consequently, we need new, preferably quick and easy instruments to collect this information, which can be very useful for online consultations and registry purposes. We compared patients’ assessments of SLE disease impact/activity, as reported by a shorter version of the Quick Systemic Lupus Activity Questionnaire (Q-SLAQ), with physicians’ assessments using SLE Activity Measure (SLAM) and SLE Disease Activity Index (SLEDAI-2K) and with the original Systemic Lupus Activity Questionnaire (SLAQ).Methods Patients with SLE (n=115), with a disease duration of 15 years (IQR 17), completed the Q-SLAQ prior to physicians’ assessments by SLAM and SLEDAI-2K. A second set of patients (n=85) with similar characteristics filled out Q-SLAQ and SLAQ. Spearman’s ρ correlations were explored between patients’ total Q-SLAQ and subscales (Symptom Score, Patient’s Global Disease Activity) and physicians’ SLAM and SLEDAI-2K, with and without laboratory items (SLAM-nolab and SLEDAI-2K-nolab) and SLAQ. Corresponding items in Q-SLAQ and SLAM were compared.Results Correlations between patients’ and physicians’ assessments were higher for SLAM-nolab (total Q-SLAQ, ρ=0.71; Symptom Score, ρ=0.67; and Patient’s Global Disease Activity, ρ=0.68) than for the original SLAM (total Q-SLAQ, ρ=0.53; Symptom Score, ρ=0.50; and Patient’s Global Disease Activity, ρ=0.53). Regarding specific symptoms, fatigue (ρ=0.72) and alopecia (ρ=0.71) correlated best, while pulmonary/respiratory symptoms correlated least (ρ=0.19, p=0.039). Physicians assessment with SLEDAI-2K-nolab correlated weakly with patients’ assessments (total Q-SLAQ, ρ=0.30; Symptom Score, ρ=0.30; and Patient’s Global Disease Activity, ρ=0.36). Bivariate correlations between Q-SLAQ and SLAQ were good (ρ=0.82–0.96).Conclusions Q-SLAQ and the original SLAQ performed equally well, demonstrating that the shorter Q-SLAQ can safely be used to monitor patients’ perception of disease impact/activity. We also noted an intriguing discrepancy between physicians’ and patients’ evaluations of pulmonary/respiratory symptoms, which requires further investigations.